KICK IT, MO! - Adler, David A.; Ricks, Sam (New York : Random House, 2018)
When soccer season starts, Mo, who has been working hard to improve his kicking skills, wonders if he will ever get a chance to show his team what he can do.
Keywords: Readers; Soccer stories -- Juvenile fiction